Uygur Autonomous Region of the People’s Republic of China - Kenesbekova, K. K. (Journal of Oriental Studies, 2016)
Relationships between between the Republic of Kazakhstan and Xinjiang This article is dedicated to the trends and specifi c characteristics of international and regional economic cooperation in the processof intensively increasing globalization, investigated the economic and trade cooperation between Republic of Kazakhstan and Xinjiang Uygur Autonomous Region of the People’s Republic of China. The purpose of this thesis is to analyze the production structure of Xinjiang and Kazakhstan, the relative comparative advantages among sectors and sub-sectors between them, and the similarities of the two economies, the best pattern of regional economic and trade cooperation; to study how to establish an extensive and comprehensive economic cooperation framework, to seek ways for developing a stable and mature business relationship between Xinjiang and Kazakhstan, and to set up a bridge for mutually benefi cial regionalcooperation between the north-western part of China and Kazakhstan.